Exploring the limitations of GDP per capita as an indicator of economic development: a cross-country perspective - Dědeček Radek; Dudzich Viktar (Review of Economic Perspectives, 2022)
In this paper, we explore the drawbacks of GDP per capita in purchasing power parity as an indicator of economic development and well-being and evaluate the factors which diminish its ability to represent the level of life. Firstly, we theoretically outline the issues that might be undermining the suitability of GDP per capita as a measure of well-being, and debate other development indicators. Subsequently, we confront GDP per capita with the most well-known development indicator – the Human Development Index HDI – and calculate the deviations between these two indicators for a panel of 141 countries. To empirically evaluate the potential limitations of GDP in measuring development, we regress the computed deviations between development and GDP on an array of economic, social, and political variables employing a heterogeneous panel dataset and robust fixed effects estimators. The results reveal that countries with higher income inequality and level of economic freedom are characterised by lower development than implied by their GDP per capita. Contrarily, the size of the shadow economy is negatively linked to the deviations of HDI from GDP. Certain sociocultural, geographic, and ecological factors, such as higher fertility rates, cold climate, and the depletion of natural resources, are prevalent among nations ranking higher in GDP per capita than in development.